Kelompok Sebaya dan Perilaku Makan Menyimpang Remaja SMA di Jakarta - Isra, Rizky Ibrahim (Masyarakat: Jurnal Sosiologi, 2016)
This article discusses the correlation between peer group pressure and eating disorder behavior symptoms in Jakarta Senior High School students. Many of studies talk about it, but the discussion about eating disorder behavior on sociology was rarely found. In this article, sex was used as a control variable while many of studies only focused on the woman. The earlier studies that only focused on female have a lack of peer group influence analysis because it is biased. Therefore the author argues that peer group pressure influences the emergence of eating disorder behavior symptoms not only to female students but also to male students. This article was written based on a study which uses quantitative methods with stratified probability random sampling on 235 students from a state senior high school in Jakarta. This article shows that there is a correlation between peer group pressure on eating disorder behavior in Jakarta senior high school students where male students more influenced by the message from his peer group, while female students more influenced by integration and likeability.